Fabrication and Properties of Thermal Sprayed AlSi-Based Coatings from Nanocomposite Powders - Limpichaipanit A. (2014)
AlSi-based nanocomposite powders (where nanoparticles were TiO2, ZrO2, and Al2O3 and the amount of reinforcement was 2.5, 5, and 10 wt.%) were made by ball milling and then thermal sprayed using low velocity oxy-fuel technique. The AlSi-based nanocomposite powders had nanosized ceramic reinforcement adhered to the surface of the powders after ball milling. The AlSi-based coatings had the typical thermal spray microstructure where lamellae, oxide layers, unmelted particles, and pores could be seen. Submicron second phase in the form of agglomerates, molten splats, or unmelted particles between AlSi lamellae could be observed as well. Hardness and porosity of the coatings increased when more ceramic second phase particles (harder than AlSi) were added. Sliding wear tests were carried out in pin-on-disk geometry. The wear tracks of AlSi and AlSi-based coatings show plastic deformation as the main material removal mechanism during the sliding wear test. The sliding wear rate of the coatings decreased as more second phase ceramic particles were added. It was due to an increase in the hardness and a decrease in the friction coefficient of the coatings. © 2012 ASM International.